PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP LOYALITAS KERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA UD. SINAR HARAPAN - Nurrachmawati, Tiarayani (Universitas Nusantara PGRI Kediri, 2023)
Abstract This research is motivated by the importance of the role of a leader in a company which is required to be able to manage all its employees and all production activities so that production results are maximized. However, the many activities of the leadership outside the company make the leadership not often within the scope of the company. This has an impact on the lack of communication between employees and leaders, has an impact on employee motivation which can result in decreased employee loyalty. The purpose of this study was to determine how much influence the variables of leadership and communication have on employee loyalty through motivation as an intervening variable at UD. Ray of hope. In this study, researchers used a causality quantitative approach by processing data using SPSS 23.0. The sampling used in this study was a purposive sampling technique, and the data collection technique in this study was based on questionnaires distributed to 40 UD employees. Sinar Harapan as a respondent. The results of this study are that the leadership and communication variables partially have a significant influence on motivation. Variables of motivation and leadership partially have a significant influence on work loyalty. Communication variable has no significant effect on work loyalty.